Eco-Printing: The Potential of an Eco-Friendly Economy in the Era of a Pandemic - Fidiana Fidiana; Widhi Ariestianti Rochdianingrum; Endang Dwi Retnani; Dini Widyawati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Eco-print is a fabric dyeing technique from ecology or plants commonly known as eco-dyeing. Eco-print aims to print patterns and colors on fabrics to produce unique, natural, and authentic motifs. The principle used is to attach flowers, leaves, stems, or other parts of plants that contain color pigments to the fabric media. Fabrics that are given motifs and colors with eco-print techniques can evolve into batik products, bags, umbrellas, and other crafts. In other words, Eco-print products do not use synthetic or chemical dyes but utilize natural patterns and colors from plant parts such as twigs, leaves, stems, and flowers. The eco-print method is thus very environmentally friendly by utilizing materials found in the surrounding environment. In addition, eco-print-based products have economic prospects during the COVID-19 pandemic because people have started to care about the environment. This product is also exclusive and unique because the motifs and colors produced are never the same. The uniqueness of the motif is unlimited depending on creativity. Each cloth has a variety of motifs according to the type and layout of the plants used. Each fabric is different from other fabrics in terms of motifs and colors. It is an economic potential that causes eco-print products to have a higher selling value than synthetic products. Thus, eco-print products are not mass products. Each product uses a set of plants as a pattern and is disposable. The primary color dyeing process, the length of steaming, the technique of placing plants on the cloth, the rolling technique, and the intensity of sunlight when drying will produce different results on each sheet of fabric, although the technique used is always the same. The print results are often unexpected and quite surprising. It is interesting and challenges eco-print craftsmen to keep experimenting to produce quality and standardized products. After the eco-print training, MSME women in Sukolilo produced batik clothes, headscarves, jute combination bags, and tablecloths. The products from this eco-print need a network to be able to reach potential markets both locally and globally